Evaluation of Nutritive Value of Some Citrus Pulp as Feedstuffs in Rabbit Diets - Ibrahim, M.R.; El-Banna, H.M.; Omara, I.I.; Suliman, Marwa A. (Pakistan Journal of Nutrition, 2011)
The present study was conducted to evaluate, determine nutrient digestibility and nutritive value of lemon pulp and orange pulp. The citrus by-products were replaced for yellow corn in the basal diet at 3 levels (20, 40 and 60%) for each by-product. A total number of 21 White New Zealand rabbits (NZW) at 8 weeks of age were individually weighed and randomly assigned individually into seven groups representing the seven experimental groups. Each group was divided into three replicates of one rabbit each. All animals were kept under the same management and hygienic conditions and were housed in metal battery cages supplied with separated feeders. Diets were offered ad-libitum and fresh water was available all times from automatic nipple drinkers. The experimental period lasted for 11 days. All rabbits were vaccinated against diseases and they were under veterinary control. The result showed that lemon and orange pulps are rich in CF, NDF, ADF, ADL, Hemi-cellulose and cellulose compared to yellow corn but CP and GE content for lemon and orange pulps are similarly equal compared to yellow corn. The content of vitamin C in lemon pulp and orange pulp was 0.068 g/100 g and 0.144 g/100 g compared with yellow corn 0.030 g/100 g, respectively. The anti-oxidant content of lemon pulp and orange pulp was 11.60 μl and 12.2 μl compared the yellow corn (8.29 μl) at 25 μl and 17.9 μl and 16.4 μl compared with 15.24 μl at 50 μl, respectively. The total saturated fatty acids content of lemon pulp and yellow corn was approximately equal but its content in orange pulp was higher than the yellow corn. Total unsaturated fatty acids content of lemon pulp and orange pulp were to be lower than that in yellow corn. There were insignificant differences in DM and Organic Matter (OM) digestibility among the experimental diets and control diet. The obtained results also that 40% substitution level of lemon pulp recorded the highest (p